2013
DOI: 10.1159/000350471
|View full text |Cite
|
Sign up to set email alerts
|

The Golgi Apparatus: Panel Point of Cytosolic Ca2+Regulation

Abstract: TheGolgi apparatus (GA), an intermediate organelle of the cell inner membrane system, plays a key role in protein glycosylation and secretion. In recent years, this organelle has been found to act as a vital intracellular Ca2+ store because different Ca2+ regulators, such as the inositol-1,4,5-triphosphate receptor, sarco/endoplasmic reticulum Ca2+-ATPase and secretory pathway Ca2+-ATPase, were demonstrated to localize on their membrane. The mechanisms involved in Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 122 publications
(189 reference statements)
0
8
0
Order By: Relevance
“…Since the level of cell activity has been directly related to the size of the GA (Lucassen et al, 1993, Salehi et al, 1995), the alterations of the GA observed in the present study would likely result in a deregulation of neuronal calcium levels (Li et al, 2013) and alterations in protein synthesis, modification, and sorting (Salehi et al, 1995, Wang et al, 2008, Xiang et al, 2013). This suggests that the defects in the GA are likely to contribute to the neurotoxicity associated with AD.…”
Section: Discussionmentioning
confidence: 79%
“…Since the level of cell activity has been directly related to the size of the GA (Lucassen et al, 1993, Salehi et al, 1995), the alterations of the GA observed in the present study would likely result in a deregulation of neuronal calcium levels (Li et al, 2013) and alterations in protein synthesis, modification, and sorting (Salehi et al, 1995, Wang et al, 2008, Xiang et al, 2013). This suggests that the defects in the GA are likely to contribute to the neurotoxicity associated with AD.…”
Section: Discussionmentioning
confidence: 79%
“…S3). The signaling lipid PI(4,5)P 2 has previously been detected on mitochondria (59), although at a much lower concentration than on the plasma membrane and in a sequestered form (59)(60)(61). We are not aware of any report showing PI4P on mitochondria.…”
Section: +mentioning
confidence: 79%
“…HHD, Hailey-Hailey disease; iTRAQ, isobaric tags for relative and absolute quantitation incorrect arrangement of intercellular adhesion molecules. 29,30 Histologically, there is impaired keratinocyte adhesion as demonstrated by acantholysis. Recent research has demonstrated that at the immunohistochemical level, there is a disassociation of the intra-and extracellular domains of epidermal keratinocyte desmosomal cadherin and E-cadherin.…”
Section: Discussionmentioning
confidence: 99%